1981
DOI: 10.1017/s0022112081000748
|View full text |Cite
|
Sign up to set email alerts
|

The effect of base bleed on vortex shedding and base pressure in compressible flow

Abstract: Experiments have been carried out to investigate the phenomenon of vortex shedding from the blunt trailing edge of an aerodynamic body in transonic and supersonic flow. The effect of a discharge of bleed air from a slot in the trailing edge has been included and the relationship between the vortex formation and base pressure has been considered.In transonic flow a small amount of bleed air was found to produce a rearward shift in the point of origin of the vortices with a consequent substantial increase in bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
21
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 3 publications
7
21
0
Order By: Relevance
“…The density auto correlations show the presence of a semi periodic vortex structure and have been measured over the Mach number range 0.6 to 1,24. These measurements complement those reported by Motallebi and Norbury [5) and Lawaczeck et al [14] , [15], 22 and add to the understanding of the complex relationship between boundary layer behaviour and trailing edge flow.…”
Section: Introductionsupporting
confidence: 85%
“…The density auto correlations show the presence of a semi periodic vortex structure and have been measured over the Mach number range 0.6 to 1,24. These measurements complement those reported by Motallebi and Norbury [5) and Lawaczeck et al [14] , [15], 22 and add to the understanding of the complex relationship between boundary layer behaviour and trailing edge flow.…”
Section: Introductionsupporting
confidence: 85%
“…A schematic view of a two-dimensional base region in supersonic conditions is represented in Figure 1. Different ways to control the base region properties have been considered, but one of particular interest is the so-called base bleed [9,10], where flow is directly injected at the base region. This type of flow control is commonly found in turbomachinery, where colder flow from the turbine blade refrigeration circuits is ejected at the trailing edge of the thin airfoils, increasing the pressure at the base region and reducing the aerodynamic losses.…”
Section: Introductionmentioning
confidence: 99%
“…The result from the previous research has proved that active control is not only a workable technology for minimizing the unstable behavior, but also the approach is easily imitated for large scale applications [6][7][8]. It was investigated that the pressure in the augmented area is related to the boundary layer type and thickness upward of the expansion [9].The effectiveness of bleed in the wake region and the flow field at higher Mach number showed that the pressure remains uniform across the plane [10,11]. Initially, the average base pressure showed a gradual increment with the bleed flow rate, and the optimal results were characterized by a weak corner expansion, minimum shear value and absence of recirculation phenomenon.…”
Section: Introductionmentioning
confidence: 99%